Vegetative reproduction and phylogeny of a new subtidal alga from Korea: Dipterocladia yongdeokkoi sp. nov. (Ceramiales, Rhodophyta). Issue 1 (2nd January 2019) - Hwang, Il Ki; Boo, Ga Hun
ABSTRACT: Dipterocladia yongdeokkoi sp. nov . was collected at depths of 6–15 m at three locations at Jeju Island, Korea: Biyangdo, Hado and Shinchang. All plants were vegetative without reproductive structures. For two years in laboratory culture, plants were consistently vegetative. Cultured plants formed single-celled diaspores and multicellular propagules that grew into mature plants. Dipterocladia yongdeokkoi is distinguished by its flattened thallus arising from a thick, cylindrical stipe, compressed axes, irregular branches and alternately pinnate determinate adventitious laterals and pseudolaterals. Analyses of mitochondrial cox 1, plastid rbc L, and nuclear small subunit (SSU) sequences support the monophyly of Dipterocladia and the distinctness of D. yongdeokkoi from other species of Dipterocladia .